Interactive STEAM-Based E-Modules in Chemistry Education: Implementation and Impact - Kartini Rahman Nisa; Wahyuningsih; Sri Astuti Rahman Coa; Jayadin; Kristina Tresia Leto (Buletin Edukasi Indonesia, 2026)
The abstract nature of chemical concepts, which are often intangible and not directly observable, makes chemistry learning challenging and can reduce overall learning quality. Integrating technology with interdisciplinary approaches, such as STEAM-based interactive e-modules, offers a promising solution to enhance chemistry education. This study aims to systematically map the implementation of STEAM-based e-modules and examine their impact on chemistry learning. A literature review method was employed, sourcing data from Google Scholar and Scopus using the keywords "STEAM E-Module" and "Chemistry Education." Findings indicate that STEAM e-modules are commonly implemented with digital tools such as Flipbook and ChemSketch, and adopt collaborative approaches incorporating Problem-Based Learning (PBL) and Project-Based Learning (PjBL) designs. The use of STEAM e-modules consistently demonstrates positive effects on students’ science literacy, academic achievement, conceptual understanding, scientific process skills, and critical thinking. These results highlight the effectiveness of interactive e-modules as a medium to enhance both cognitive and higher-order skills in chemistry education.